Two methods for amplifying the optical nonlinearity of a conjugated porphyrin polymer: transmetallation and self-assembly - Screen, T; Thorne, J; Denning, R; Bucknall, D; Anderson, H (2003)
A new soluble conjugated metalloporphyrin polymer has been synthesised as its complex with zinc(II), lead(II) and copper(II) and as the free-base. The zinc complex aggregates in non-coordinating solvents, due to coordination of the amide side-chains to the zinc centres. These aggregates dissociate on addition of pyridine to give single-strand complexes; the dissociation process displays an amazingly high positive cooperativity (Hill coefficient: n H = 3.2 at 50% sat., rising to 11.5 at 95% sat.). The zinc polymer binds 4,4′-bipyridyl to form a double-strand ladder complex; this self-assembly process holds neighbouring porphyrins coplanar and increases the π-conjugation, resulting in a red-shift in the electronic absorption. Degenerate four wave mixing, at 1064 nm, was used to characterise the optical nonlinearity of these polymers. Both the real and imaginary parts of the third-order susceptibility χ(3) are strongly amplified in the lead(II) complex and in the double-strand assembly. We estimate that the two-photon absorption cross-section of the ladder complex is 5 x 104 GM per macrocycle at 1064 nm, which is an order of magnitude higher than the highest values reported for other chromophores, suggesting that these polymers may be relevant to a variety of applications including photodynamic therapy.